Experimental study of vibration characteristics of 110 kV oil-immersed transformer. (June 2021) - Li, Xiang; Mo, Juan; Ma, Yuchao; Lu, Ling
As the voltage level and capacity of power transformer continue to rise, this results in its increasingly prominent vibration and noise problems. In this article, we study the vibration characteristics of the 110-kV oil-immersed transformer by means of experiments. Under different no-load voltages and short-circuit currents, the vibration signals in different positions and directions of the transformer are monitored respectively, and the vibration laws are analyzed. First, the vibration law of transformers is closely related to the operating conditions of transformers, which directly affects the frequency components of transformer vibration and the amplitude corresponding to different frequencies; second, it is found that the vibration law of transformers facing different directions will change under different operating conditions; and third, it summarizes the vibration of transformers in different positions under different operating conditions. These results can not only be used as the experimental basis for the theoretical research on large-scale transformer noise but also provides experimental support for the research on vibration reduction and noise reduction methods of large-scale transformer in engineering.